ALGORITHMS FOR AUTOMATION OF PROCESSING OF THE ALLOYS MACRO- AND MICROSTRUCTURE - A. N. Chichko; O. A. Sachek; V. A. Ganzha; O. P. Gashnikova (Литьë и металлургия)
Analysis of modem methods of the pictures processing automation is presented. The ways of machinery determination of such defects as center segregation, liquating striations and cracks and development of algorithms of macro-and microstructures of alloys of industrial production process are shown at the example of the task of processing of macrostructure of template of industrial production slugs.